Safety findings from Phase 3 lasmiditan studies for acute treatment of migraine: Results from SAMURAI and SPARTAN - Krege, John H (Cephalalgia, 2019)
BACKGROUND: We assessed the safety profile of lasmiditan, a selective 5-HT(1F) receptor agonist without vasoconstrictive activity being developed as an acute therapy for migraine. METHODS: SAMURAI and SPARTAN were Phase 3 double-blind studies of patients with migraine, randomized to oral lasmiditan 50 mg (SPARTAN only), 100 mg, 200 mg, or placebo to be taken within 4 hours of onset of migraine pain. Safety data from the studies were integrated. Treatment-emergent adverse events (occurring within 48 hours of first dose) were considered in the analyses. RESULTS: The safety population comprised 1262 patients assigned placebo, and 654, 1265, and 1258 assigned lasmiditan 50 mg, 100 mg, and 200 mg, respectively. There were no deaths; serious adverse events were reported for seven patients (placebo, n = 2 [0.2%]; lasmiditan 50 mg, n = 1 [0.2%]; lasmiditan 100 mg, n = 1 [0.2%]; lasmiditan 200 mg, n = 3 [0.2%]). Patients reporting ≥ 1 treatment-emergent adverse events were: Placebo, n = 174 (13.5%); lasmiditan 50 mg, n = 166 (25.4%); lasmiditan 100 mg, n = 458 (36.2%); and lasmiditan 200 mg, n = 510 (40.6%). Treatment-emergent adverse events were generally mild or moderate in severity. The most common treatment-emergent adverse events with lasmiditan were dizziness, paresthesia, somnolence, fatigue, nausea, muscular weakness and hypoesthesia. There were no ischemic events. CONCLUSIONS: As a centrally-penetrant drug, lasmiditan use was associated with neurologic treatment-emergent adverse events; most were mild or moderate in severity and self-limiting. TRIAL REGISTRATION AT CLINICALTRIALS.GOV: SAMURAI (NCT02439320) and SPARTAN (NCT02605174).